Detailed chemical modelling of a flameless combustion turbine for pollution prevention. (24th April 2008) - Hamdi, M.; Benticha, H.; Sassi, M.
Flameless combustion has been acknowledged as one of the most interesting combustion technologies to meet both the targets of high process efficiency and low pollutant emissions. The present investigation is concerned with the application of the flameless combustion mode to an adiabatic combustor, typically used in gas turbine engines. Detailed chemical kinetics calculations, by means of a specific zero dimensional loop reactor model, have been performed to analyse its chemical aspects. The main objective of this study is to provide a fundamental understanding of the physical and chemical processes that occur during combustion in high-temperature air or exhaust gases with a low content of oxygen. The detailed chemistry approach, based on the comprehensive (GRI_MECH3.0 mechanism) oxidation kinetics of methane, is used. Simulation results clearly illustrate that even at high operating temperatures and pressures, NOx emissions could be reduced by flameless combustion to very low levels. The flameless oxidation then appears as a promising technique for industrial gas turbine combustor applications.